Republic of Moldova : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 2001)
This paper analyzes the recent economic developments in Moldova by reviewing the real, fiscal, and external sectors developments; money banking; and structural policies. The study provides a statistical analysis on the composition of fiscal adjustments in the country, and describes the recent trends in social spending and social indicators in Moldova and in other transition economies in the 1990s, the methodology for estimating efficiency in public spending on education and health care, and assesses the current account determination in the country.